Tourism and management study programme through blended learning: development and results. (4th May 2018) - Simonova, Ivana
Abstract: This paper introduces and discusses a tourism and management study programme at the Faculty of Informatics and Management (FIM), University of Hradec Králové. It begins with description of the programme, along with a summary of its history and is considered in the light of changes in accreditation requirements. Students′ interest in the programme and foreign language skills gradually waned over a period of time. The number of students taking the state exams in foreign languages and their grades were used as indicators of students′ interest. We adopted blended learning but this did not increase interest in studying foreign languages. The blended learning model and its results in the Czech context are discussed with reference to experiences gained by others from around the world. We aim to verify whether changes to the learning content covering theory and practice enhance the quality and attractiveness of the tourism and management study programme.